Clinical performance of an alkasite-based bioactive restorative in class II cavities: a randomized clinical trial - Fatma Dilsad OZ; Ece MERAL; Sevil GURGAN (University of São Paulo, 2023)
Abstract Objective This clinical study aimed to evaluate the clinical performance of an alkasite-based bioactive material by comparing it with a resin composite (RC) in the restoration of Class II cavities over a year. Methodology A hundred Class II cavities were restored at 31 participants. Groups were as follows: Cention N (CN) (Ivoclar Vivadent, Schaan, Liechtenstein) and G-ænial Posterior (GP) (GC, Tokyo, Japan) in combination with G-Premio Bond (etch&rinse). Restorative systems were applied following manufacturers' instructions. They were finished and polished immediately after placement and scored based on retention, marginal discoloration, marginal adaptation, sensitivity, surface texture, and color match using modified USPHS criteria after 1 week (baseline), 6 months, and 12 months. Statistical analyses were performed using chi-square, McNemar's, and Kaplan Meier tests. Results After 12 months, the recall rate was 87%. Survival rates of CN and GP restorations were 92.5% and 97.7%, respectively. Three CN and one GP restorations lost retention. Seven CN (17.9%) and five (11.6%) GP restorations were scored as bravo for marginal adaptation and no significant difference was seen between groups (p=0.363). One (2.7%) CN and two GP (4.7%) restorations were scored as bravo for marginal discoloration, but no significant difference was observed between groups(p=1.00). For surface texture, three (8.1%) CN and three (7%) GP restorations were scored as bravo (p=1.00). None of the restorations demonstrated post-operative sensitivity or secondary caries at any examinations. Conclusion The tested restorative materials performed similar successful clinical performances after 12 months. ClinicalTrials.gov (NTC04825379).